2017
DOI: 10.1177/1934578x1701200631
|View full text |Cite
|
Sign up to set email alerts
|

Prospection of Effects of Guava Leaves Infusion: Antigenotoxic Action and Enzymatic Inhibition

Abstract: Several forms of Psidium guajava L. (guava) leaf preparations have been widely used for prevention and treatment of illnesses. However, researches about the protective action of guava's natural products on the genetic material of animal cells is scarce. Accordingly, the aim of this study was to evaluate the antigenotoxic potential of infusions of guava leaves from three cultivars (Pedro Sato, Paluma and Roxa) against DNA damage induced by Doxorubicin (DXR) in human leukocytes, and their effects on enzymatic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Cesar et al (43) demonstrated the absence of DNA fragmentation in human leukocytes, using the aqueous extracts of different cultivars from Psidium guajava, even when evaluated at a high concentration (300 μL mL -1 ). In addition, nucleoids treated with these extracts decreased by 75% the frequency of DNA damage (induced by doxorubicin), demonstrating their antigenotoxic potential.…”
Section: Continuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cesar et al (43) demonstrated the absence of DNA fragmentation in human leukocytes, using the aqueous extracts of different cultivars from Psidium guajava, even when evaluated at a high concentration (300 μL mL -1 ). In addition, nucleoids treated with these extracts decreased by 75% the frequency of DNA damage (induced by doxorubicin), demonstrating their antigenotoxic potential.…”
Section: Continuesmentioning
confidence: 99%
“…Semina: Ciências Biológicas e da Saúde, Londrina, v. 43, n. 1, p. 101-118, jan./jun. 2022 to cure digestive and inflammatory issues.…”
Section: Introductionunclassified